Ibn Abi Jamrah Methodology in Explaining the Hadith of Bahjatu al-Nufus | منهج ابن أبي حمزة في شرح أحاديث كتاب بهجة النفوس - Inaratul 'ayn (Al-Zahra : Journal for Islamic and Arabic Studies, 2017)
This study discusses Imam Ibn Abi Jamrah and the method of writing his book “Bahjatu al-Nufus”. The book, whose full name is Bahjatu al-Nufus wa Tahalliha bi Ma'rifati Ma Laha wa Ma 'Alayha is one of the most important explanatory books (syarah) of the Prophet's hadith in our Islamic literature. Imam Abdullah ibn Abi Jamrah previously wrote the book Jam'u al-Nihayah fi Bid'i al-Ghayr wa Ghayah where he chose 296 traditions from Sahih Bukhari. Later, he wrote Bahjatu al-Nufus as a syarah of these chosen traditions, beginning with the explanation of the language side, and the explanations of jurisprudence and morals. Bahjatu al-Nufus emphasized the multiplication of advantages in every similar hadith and collected in a chapter. And the textual meaning from the hadith content (matn) is a gateway to the explanation of meaning.